A Self‐Assembled DNA Origami‐Gold Nanorod Complex for Cancer Theranostics. Issue 38 (6th August 2015) - Jiang, Qiao; Shi, Yuefeng; Zhang, Qian; Li, Na; Zhan, Pengfei; Song, Linlin; Dai, Luru; Tian, Jie; Du, Yang; Cheng, Zhen; Ding, Baoquan
<x xml:space="preserve">Abstract</x> A self‐assembled DNA origami (DO)‐gold nanorod (GNR) complex, which is a dual‐functional nanotheranostics constructed by decorating GNRs onto the surface of DNA origami, is demonstrated. After 24 h incubation of two structured DO‐GNR complexes with human MCF7 breast cancer cells, significant enhancement of cell uptake is achieved compared to bare GNRs by two‐photon luminescence imaging. Particularly, the triangle shaped DO‐GNR complex exhibits optimal cellular accumulation. Compared to GNRs, improved photothermolysis against tumor cells is accomplished for the triangle DO‐GNR complex by two‐photon laser or NIR laser irradiation. Moreover, the DO‐GNR complex exhibits enhanced antitumor efficacy compared with bare GNRs in nude mice bearing breast tumor xenografts. The results demonstrate that the DO‐GNR complex can achieve optimal two‐photon cell imaging and photothermal effect, suggesting a promising candidate for cancer diagnosis and therapy both in vitro and in vivo.